El hospital psiquiátrico en diálogos atemporales - Emerich, Bruno Ferrari; Yasui, Silvio [UNESP] (FapUNIFESP (SciELO), 2016)
This paper aims to present a dialogue between two militants of the Brazilian Psychiatric Reform who talked about immersion in the daily life of psychiatric hospitals, but from experiences that were acquired in different hospitals and at different times: Vera Cruz, in the city of Sorocaba, in 2012; and Juquery, in São Paulo, during the 1980s. In 2012, Bruno experienced an intervention process within the reality of a psychiatric ward that Silvio had expected to have been surmounted. While respecting the differences in places and in experiences that they have been through, their conclusion is that the treatment model proposed by psychiatric hospitals has erased the boundaries of time and has led to similar realities that mortify subjects and naturalize segregation practices.
O hospital psiquiátrico em diálogos atemporais
The psychiatric hospital in timeless dialogues
Keywords: Brazilian psychiatric reform; Deinstitutionalization; Madness; Psychiatric hospitals